Thank you for the opportunity to help you with your question!
Ok thanks a lot man.
given x ->0 [ 1/r + 1/x-r ] / x
so for your understanding first take 1/r + 1/x-r and simplify
1/r + 1/x-r = [ x-r +r ] / (r) * (x-r)
= x / (r) * (x-r)
now plug it in the actual problem x -->0 x / (r) * (x-r) *x
in the numerator and denominator we have x , so both will get cancel
x ->0 [ 1/r + 1/x-r ] / x = 1 / (r) * (x-r)
so now plug x =0
we will get = 1 / (r) * (0 -r)
= 1 / ( r) * (-r)
= - 1 / (r^2)
I hope understand it well. If not comment but don't forget to rate me and give me more and more questions. thanks
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?